2005
DOI: 10.1187/cbe.04-06-0042
|View full text |Cite
|
Sign up to set email alerts
|

Understanding of Genetic Information in Higher Secondary Students in Northeast India and the Implications for Genetics Education

Abstract: Since the work of Watson and Crick in the mid-1950s, the science of genetics has become increasingly molecular. The development of recombinant DNA technologies by the agricultural and pharmaceutical industries led to the introduction of genetically modified organisms (GMOs). By the end of the twentieth century, reports of animal cloning and recent completion of the Human Genome Project (HGP), as well techniques developed for DNA fingerprinting, gene therapy and others, raised important ethical and social issue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
1
12

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 24 publications
3
29
1
12
Order By: Relevance
“…Saka et al, (2006) and Dikmenli (2010) studies showed that teachers were unsatisfied to make connection on the molecular biology concepts. The similar finding was found by Chattopadhyay (2005) that students were unable to connect their understanding of gene with the chromosom. Marbach-Ad (2001) reported that twelfth grade students experience extensive difficulties in relating genetic concepts and they did not connect the concepts of gene and trait to more molecular concepts such as DNA, RNA and proteins.…”
Section: Resultssupporting
confidence: 73%
“…Saka et al, (2006) and Dikmenli (2010) studies showed that teachers were unsatisfied to make connection on the molecular biology concepts. The similar finding was found by Chattopadhyay (2005) that students were unable to connect their understanding of gene with the chromosom. Marbach-Ad (2001) reported that twelfth grade students experience extensive difficulties in relating genetic concepts and they did not connect the concepts of gene and trait to more molecular concepts such as DNA, RNA and proteins.…”
Section: Resultssupporting
confidence: 73%
“…Those difficulties encountered by students may be attributed to two main factors: the difficulty of grasping biology concepts and "working scientifically" skills, and the overloaded curriculum.Studies have reported that students face difficulties in many abstracts concepts or topics in biology, at both high schools and university levels, including the concepts of hormones, cells, genes and chromosomes, mitosis and meiosis, and the nervous system (Agboghoroma and Oyovwi, 2015, Agorram et al, 2010, Chattopadhyay, 2005and Tekkaya et al, 2001, in addition to other topics like water and gas transport in plants, protein synthesis, photosynthesis and respiration, gaseous exchange, energy, organs, physiological processes and oxygen transport (Çimers, 2012). Adding to the abstract content, the nature of science itself, which requires learning and applying "working scientifically skills" throughout the course of study, is a major problem for students.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that many of the incorrect ideas that students have in genetics originate in middle school and high school (AAAS 1993). High school students from different countries appear to share a suite of incorrect ideas, including not understanding the relationship between a gene, a chromosome, and a cell; thinking that different cells contain different genes; not understanding how genetic information is transmitted; and concluding that single genes are responsible for complex traits such as height Chattopadhyay 2005;Mills-Shaw et al 2008;Boujemma et al 2010). Some of these incorrect ideas may be perpetuated by K-12 teachers who do not have an adequate understanding of the complexities of genetics, particularly with regard to how concepts relate to each other (Cakir and Crawford 2001).…”
mentioning
confidence: 99%
“…There are a variety of ways to probe common conceptual difficulties among genetics students, including multiple-choice questions with written explanations (e.g., Lewis and WoodRobinson 2000;Chattopadhyay 2005), short answer questions (e.g., Mills-Shaw et al 2008;Boujemma et al 2010), and think-aloud student interviews (e.g., Lewis and Kattman 2004). Written responses to questions and think-aloud interviews can provide valuable input on student thinking and dissecting student understanding, but are not always practical to administer and score in a large enrollment undergraduate genetics course.…”
mentioning
confidence: 99%